The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1055/s-0042-124361
|View full text |Cite
|
Sign up to set email alerts
|

Primary Fetal Lung Hypoplasia (PFLH): Imaging and Clinical Characteristics

Abstract: To describe in utero and postnatal imaging and clinical characteristics of primary fetal lung hypoplasia (PFLH). A retrospective review of fetuses and neonates diagnosed in one academic tertiary center during an eleven-year period. 12 cases of PFLH were identified. 4 were bilateral and 8 had unilateral involvement. Prenatal sonographic characteristics, postnatal magnetic resonance imaging (MRI), computerized tomographic angiography (CTA), and histologic findings are described. 3 of the 4 bilateral cases were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Triebwasser et al [2] conducted a systematic review of the value of two-dimensional ultrasound parameters in the evaluation of pulmonary hypoplasia, reporting that the TC, TC/AC, and lung area have clinical value in the diagnosis of pulmonary hypoplasia and that the lung area has excellent predictive accuracy (sensitivity 78-81%, specificity 75-100%). The Aafreen S [24] and Achiron R [25] studies reported that the right lung area was significantly smaller in patients with pulmonary dysplasia. Therefore, it is of great clinical value to establish the reference values of the lung area in the Chinese population.…”
Section: Discussionmentioning
confidence: 98%
“…Triebwasser et al [2] conducted a systematic review of the value of two-dimensional ultrasound parameters in the evaluation of pulmonary hypoplasia, reporting that the TC, TC/AC, and lung area have clinical value in the diagnosis of pulmonary hypoplasia and that the lung area has excellent predictive accuracy (sensitivity 78-81%, specificity 75-100%). The Aafreen S [24] and Achiron R [25] studies reported that the right lung area was significantly smaller in patients with pulmonary dysplasia. Therefore, it is of great clinical value to establish the reference values of the lung area in the Chinese population.…”
Section: Discussionmentioning
confidence: 98%